Essential oil-grafted copper nanoparticles as a potential next-generation fungicide for holistic disease management in maize - Dorjee, Lham; Gogoi, Robin; Kamil, Deeba; Kumar, Rajesh; Mondal, Tapan Kumar; Pattanayak, Sudeepta; Gurung, Bishal (Frontiers in Microbiology, 2023)
Sustainable food production is necessary to meet the demand of the incessantly growing human population. Phytopathogens pose a major constraint in food production and the use of conventional fungicides to manage them is under the purview of criticism due to their numerous setbacks. In the present study, essential oil-grafted copper nanoparticles (EGC) were generated, characterized, and evaluated against the maize fungal pathogens viz., Bipolaris maydis, Rhizoctonia solani f. sp. sasakii, Macrophomina phaseolina, Fusarium verticillioides, and Sclerotium rolfsii. The ED50 for the fungi under study ranged from 43-56 µg ml-1 and significant inhibition was observed at a low dose of 20 µg ml-1 under in vitro conditions. Under net house conditions, seed treatment + foliar spray at 250 and 500 mg L-1 of EGC performed remarkably against maydis leaf blight (MLB), with reduced percent disease index (PDI) by 27.116 and 25.292 %, respectively in two Kharif seasons (May-Sep, 2021, 2022). The activity of enzymatic antioxidants viz., β-1, 3-glucanase, PAL, POX, PPO, and a non-enzymatic antioxidant (total phenolics) were increased in treated maize plants, indicating host defence was triggered. The optimum concentrations of EGC (250 mg L-1 and 500 mg L-1) exhibited improved physiological characteristics such as photosynthetic activity, shoot biomass, plant height, germination percentage, vigour index, and root system traits. However, higher concentrations of 1000 mg L-1 rendered phytotoxicity, reducing growth, biomass, and copper bioaccumulation to high toxic levels, mainly in the foliar-sprayed maize leaves. Also, EGC and copper nanoparticles (CuNPs) at 1000 mg L-1, reduced the absorption and concentration of manganese and zinc indicating a negative correlation between Cu and Mn/Zn. Our study proposes, the CuNPs combined with EO (Clove oil) exhibit astounding synergistic efficacy against maize fungal pathogens and optimized concentrations can be used as an alternative to commercial fungicides without any serious impact on environmental health.